2017
DOI: 10.1186/s12879-017-2358-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk among Chinese antiretroviral-naïve adults with advanced HIV disease

Abstract: BackgroundCardiovascular disease (CVD) is an important cause of mortality among HIV-infected patients, however little is known about the burden of CVD among this population in Asia. We sought to quantify prevalence of CVD risk factors, 10-year CVD risk, and patterns of CVD risk factor treatment in a group of individuals with HIV in China.MethodsWe retrospectively analyzed baseline data from treatment-naïve HIV-infected adults enrolled in two multicenter clinical trials in China. Data regarding CVD risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
0
13
2
Order By: Relevance
“…We classified body mass index (BMI) using the following categories: underweight < 18.5, normal 18.5-24.9, overweight 25-29.9, and obese ≥30.0 kg/m 2 [18]; and dyslipidemia using the following categories: total cholesterol > 5.2 mmol/l, high-density lipoprotein cholesterol (HDL-c) < 1.0 mmol/l, low-density lipoprotein cholesterol > 4.1 mmol/l, or triglycerides > 1.7 mmol/l [19]. Participants were classified as diabetic if they had a prior diagnosis of diabetes, a fasting plasma glucose ≥7.0 mmol/l or were being treated with insulin or oral hypoglycemic agents [12]. Renal function was assessed by the estimated glomerular filtration rate (eGFR) using the formula from the Chronic Kidney Disease Epidemiology Collaboration [20], and categorized following the chronic kidney disease criteria [21].…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified body mass index (BMI) using the following categories: underweight < 18.5, normal 18.5-24.9, overweight 25-29.9, and obese ≥30.0 kg/m 2 [18]; and dyslipidemia using the following categories: total cholesterol > 5.2 mmol/l, high-density lipoprotein cholesterol (HDL-c) < 1.0 mmol/l, low-density lipoprotein cholesterol > 4.1 mmol/l, or triglycerides > 1.7 mmol/l [19]. Participants were classified as diabetic if they had a prior diagnosis of diabetes, a fasting plasma glucose ≥7.0 mmol/l or were being treated with insulin or oral hypoglycemic agents [12]. Renal function was assessed by the estimated glomerular filtration rate (eGFR) using the formula from the Chronic Kidney Disease Epidemiology Collaboration [20], and categorized following the chronic kidney disease criteria [21].…”
Section: Definitionsmentioning
confidence: 99%
“…Limited studies have focused on hypertension prevalence among PLWH in Asia [12][13][14], and these have all been cross-sectional in design. We previously reported the prevalence of hypertension was 8.4% among Chinese ART-naïve PLWH [12], which is lower than that reported in the USA and Europe [3]. However, the incidence of hypertension among PLWH in Asia, particularly after initiation of ART, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The limited literature suggests that CVD risks (e.g. carotid intima-media thickness [cIMT], chronic kidney disease [CKD], hypertension, glycometabolism abnormities) are prevalent among HIV-infected patients in China (16)(17)(18), but data for ECG manifestations in this population are lacking. To fill this gap, we conducted a cross-sectional study to investigate the prevalence and correlates of ECG abnormalities among PLWH in Shanghai.…”
mentioning
confidence: 99%
“…The prevalence of hypertension observed among ART-naive PLWH in the present study was lower than that reported in the Chinese general population (26.9%), among a nationally representative sample of over 90,000 Chinese adults from 2007-2008 (24). This might be attributable to lower BMI and prevalence of smoking among Chinese ART-naïve PLWH in the present study compared with the general population cohort, or to differences in other risk factors between the time periods during which the two cohorts were enrolled (12,25). The prevalence of hypertension observed in our study was also lower than that reported by Ding et al among Chinese PLWH (23.8%), however that study was carried out in a single study site in Zhejiang province, and included both ART-naïve and ART-experienced PLWH (13).…”
Section: Discussionmentioning
confidence: 73%